2021
DOI: 10.1016/j.strueco.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal policy and structural transformation in developing economies

Abstract: Developing economies with high levels of open or hidden unemployment face structural transformation problems. Unlike in mature economies there are no structural aggregate demand problems, and sustained aggregate demand stimulus can lead to a pro…t squeeze in the modern sector and deindustrialization. Adaptations of 'functional …nance'to developing economies should aim to stabilize the level and composition of demand at values that are consistent with a target rate of growth of the modern sector. Populist tempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Every government changes its expenditure levels in relation to its revenue collection through the use of fiscal policy, which aims to both monitor and have a favorable impact on the economy of the country (Zhongming et al, 2018). According to economic literature, fiscal policy is a crucial and significant tool for influencing a nation's overall demand (Skott, 2021). It is understood that variations in the levels, variations in timing, and variations in the makeup of government expenditure and taxation do have a big impact on how the economy is doing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Every government changes its expenditure levels in relation to its revenue collection through the use of fiscal policy, which aims to both monitor and have a favorable impact on the economy of the country (Zhongming et al, 2018). According to economic literature, fiscal policy is a crucial and significant tool for influencing a nation's overall demand (Skott, 2021). It is understood that variations in the levels, variations in timing, and variations in the makeup of government expenditure and taxation do have a big impact on how the economy is doing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fiscal policy is often used by governments to encourage robust, long-term growth and to lower poverty. During the recent global economic crisis, when governments intervened to stabilize financial institutions, spur growth, and lessen the crisis's effects on vulnerable individuals, the function and goals of fiscal policy rose to prominence (see Adelowokan, 2021;Skott, 2021) in influencing various macroeconomic indicators. The research includes the connection between fiscal policy and growth (Matallah & Matallah, 2017;Nabieu et al, 2021;Ubi-Abai & Ekere, 2018), the financial market (Akitoby & Stratmann, 2008;Dumičić, 2019;Marfatia et al, 2020;Tagkalakis, 2011), and the environment (Akbar et al, 2021;Kamal et al, 2021;Katircioglu & Katircioglu, 2018;Yuelan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The author recommends that the government of Kenya should consider rationalizing tax incentives. Skott (2021) found that the growth rate also affects the debt ratio. In other words, the higher the growth rate, ceteris paribus, the lower the asymptomatic debt ratio.…”
Section: Literature On Tax Incentivesmentioning
confidence: 99%
“…In dual economies, the main supply side constraint comes from the capital stock rather than the supply of labor, and full employment (in the modern sector) is not a feasible short‐run target. Policy makers have to define a growth target for the modern sector, weighing the benefits of fast accumulation against the cost of foregoing current consumption (Skott, 2021). Once a target for the growth rate has been defined, aggregate demand policy is left to steer the economy to—and then stabilize it at—a growth path with accumulation at the target rate and the utilization rate at the desired rate.…”
Section: Introductionmentioning
confidence: 99%